11th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference 2011
DOI: 10.2514/6.2011-6986
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Airport Performance using Surface Surveillance Data: A Case Study of BOS

Abstract: Detailed surface surveillance datasets from sources such as the Airport Surface Detection Equipment, Model-X (ASDE-X) have the potential to be used for analysis of airport operations, in addition to their primary purpose of enhancing safety. In this paper, we describe how airport performance characteristics such as departure queue dynamics and throughput can be analyzed using surface surveillance data. We also propose and evaluate several metrics to measure the daily operational performance of an airport, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…At Boston Logon International Airport, Simaiakis et.al. [3][4] field tested a concept for metering the number of flights allowed to push back from the gate onto the airport taxiway. Results showed that the concept was able to save 3,900-4,900 US gallons of fuel during four eight-hour tests by decreasing the taxi time, with a increase in gate departure delay of 4.3 minutes per flight on average.…”
Section: Introductionmentioning
confidence: 99%
“…At Boston Logon International Airport, Simaiakis et.al. [3][4] field tested a concept for metering the number of flights allowed to push back from the gate onto the airport taxiway. Results showed that the concept was able to save 3,900-4,900 US gallons of fuel during four eight-hour tests by decreasing the taxi time, with a increase in gate departure delay of 4.3 minutes per flight on average.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the data can be used to characterize surface flows, including identification of congestion hotspots, queue dynamics and departure throughput, and to develop metrics to evaluate the daily and long-term operational performance of an airport under different operating conditions. These metrics can provide useful feedback on operational performance to airport operators, and therefore have the potential to improve the efficiency of surface operations at airports [42,45].…”
Section: Metrics To Characterize Airport Operational Performancementioning
confidence: 99%
“…Aircraft wheels-off times are typically captured with a precision of seconds. In addition, ASDE-X data can be used to measure the precise number of aircraft that are physically present in the queuing area at the departure runway threshold [10,11]. As a result, runway inter-departure times can be measured conditioned on the actual state of the departure queue.…”
Section: Data Sourcesmentioning
confidence: 99%